Esketamine prevents propofol-induced injection pain: Randomized controlled trial - Xu, Chaozhi; Wei, Xiaotang; Zhang, Cuiwen; Huang, Xiaofang; Lan, Hongmeng; Xu, Yanping; Wu, Xiaoyan; Li, Fuping; Guan, Xuehai (Frontiers in Pharmacology, 2022)
Background: Propofol is widely used during anesthesia. However, propofol-induced injection pain (PIP) is considered an unpleasant perioperative outcome. This study aimed to investigate the efficacy of a mixture of esketamine and propofol in preventing propofol injection pain in patients undergoing general anesthesia. Methods: This was a prospective, double-blind, multicenter, randomized controlled trial. We included 252 adult patients with American Society of Anesthesiologists physical status I to II who underwent surgery under general anesthesia. Patients were randomly allocated in a 1:1:1:1 ratio to four groups (n=63 per group). Group NS received a mixture of 1% propofol (20 ml) and 0.9% normal saline (1 ml), group ESK-4 received a mixture of 1% propofol (20 ml) and esketamine 4 mg (diluted with 0.9% normal saline, 1 ml), group ESK-12 received a mixture of 1% propofol (20 ml) and esketamine 12 mg (diluted with 0.9% normal saline, 1 ml), and group ESK-20 received a mixture of 1% propofol (20 ml) and esketamine 20 mg (diluted with 0.9% normal saline, 1 ml) as sedative drugs during the anesthesia. The primary outcome was the incidence and distribution of different degrees of PIP. The secondary outcomes were vital signs, characteristics of surgery and anesthesia, and adverse events. Results: The incidence of PIP in group ESK-20 (33.3%) was significantly lower than that in groups NS, ESK-4, and ESK-12 (63.3%, 62.2%, and 49.1%, respectively; p<0.01). The incidence of moderate PIP in group NS (33.3%) and group ESK-4 (22.6%) was higher than that in group ESK-12 (7.5%) and ESK-20 (6.7%). The incidence of severe PIP in group NS (6.7%) and group ESK-4 (9.4%) was higher than that in group ESK-12 (1.9%) and ESK-20 (0%). There were no differences in the vital signs, characteristics of surgery and anesthesia, or adverse events between the groups. Conclusion: Our results indicate that the esketamine-propofol admixture reduced the incidence of PIP in patients undergoing general anesthesia without severe side effects.